2016
DOI: 10.1007/s00402-016-2440-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of infrapatellar fat pad resection on outcomes post-total knee arthroplasty: a systematic review

Abstract: This systematic review is limited by the lack of level one randomised controlled trials (RCTs). There is however moderate level evidence that IPFP resection increases post-operative knee pain. Further level one RCTs are required to produce evidence-based guidelines regarding IPFP resection. Systematic Review Level of Evidence: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 21 publications
0
35
2
Order By: Relevance
“…As matter of fact, IFP is well innervated: peptidergic C‐ and substance P positive nerve fibers have been found in this adipose tissue (Clockaerts et al, ; Ioan‐Facsinay and Kloppenburg, ). In 2016, two interesting systematic reviews have focused the attention on the resection/preservation of IFP during total knee replacement (TKR) (White et al, ; Ye et al, ). It has been estimated that IFP removal occurs in 88% of TKR (White et al, ), even if it still remains a matter of surgeon preference.…”
Section: Obesity and Related Comorbidities In Koamentioning
confidence: 99%
“…As matter of fact, IFP is well innervated: peptidergic C‐ and substance P positive nerve fibers have been found in this adipose tissue (Clockaerts et al, ; Ioan‐Facsinay and Kloppenburg, ). In 2016, two interesting systematic reviews have focused the attention on the resection/preservation of IFP during total knee replacement (TKR) (White et al, ; Ye et al, ). It has been estimated that IFP removal occurs in 88% of TKR (White et al, ), even if it still remains a matter of surgeon preference.…”
Section: Obesity and Related Comorbidities In Koamentioning
confidence: 99%
“…Postoperative pain is a common source of patient dissatisfaction [2]. The results of this study showed a significant reduction in postoperative pain and better recovery of post-operative knee flexion.…”
Section: Commentarymentioning
confidence: 49%
“…4 We demonstrated that the greatest benefit in reduced postoperative pain is beyond 6 months post TKA; incorporating results for one small, high quality randomised controlled trial by Pinsornsak et al 5 and two larger low quality studies. 6 7 At 5.1 years, the incidence of knee pain was almost halved in the preservation group.…”
mentioning
confidence: 73%